PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, FINANCIAL LEVERAGE, DAN NET PROFIT MARGIN TERHADAP PERATAAN LABA - Sudarmadi, Rispantyo & Muhammad Rofiq Sunarko (Universitas Slamet Riyadi, 2017)
The purpose of this study was to analyze: the effect of firm size, profitability,financial leverage and net profit margin on income smoothing. This research is acase study on a company's real estate and properties listed in the Indonesia StockExchange for the period 2012-2015. The type of data using quantitative andqualitative data. Source data using secondary data. The study population 42companies real estate and properties are listed on the Stock Exchange and the wholeis used as a sample with a total sampling technique. Collecting data used the methodof documentation. Data were analyzed used logistic regression. The results showedthat the firm size has negative and no significant effect on the income smoothing.Profitability has negative and significant effect on income smoothing. Financialleverage has negative and significant negative effect on the income smoothing. Netprofit margin has positive and significant effect on income smoothing.Keywords: firm size, profitability, financial leverage, net profit margin, incomesmoothing